Creative Activities for Work Teams and Communities of Practice. A guide for designing participatory, productive, and engaging sessions - and AKF (2023)
This free guide aims to build the skills and confidence of people designing and facilitating participatory, productive, and engaging workshop sessions for work teams and communities of practice by providing them with a series of creative activities that can be run in-person or virtually. By the time they have gone through this guide, session leads will be able to: Describe ways in which creative activities can be of value to teams and communities of practice, Design both in-person and virtual workshop sessions that incorporate creative activities, Facilitate participatory, productive and engaging workshop sessions that incorporate one or several creative activities, and Lead an effective debrief following a creative activity. This toolkit was developed by the Aga Khan Foundation.